Feel the noise: Mid-air ultrasound haptics as a novel human-vehicle interaction paradigm. - Large, David R.; Harrington, Kyle; Burnett, Gary; Georgiou, Orestis (Applied Ergonomics, 2019)
Focussed ultrasound can be used to create the sensation of touch in mid-air. Combined with gestures, this can provide haptic feedback to guide users, thereby overcoming the lack of agency associated with pure gestural interfaces, and reducing the need for vision - it is therefore particularly apropos of the driving domain. In a counter-balanced 2 × 2 driving simulator study, a traditional in-vehicle touchscreen was compared with a virtual mid-air gestural interface, both with and without ultrasound haptics. Forty-eight experienced drivers (28 male, 20 female) undertook representative in-vehicle tasks - discrete target selections and continuous slider-bar manipulations - whilst driving. Results show that haptifying gestures with ultrasound was particularly effective in reducing visual demand (number of long glances and mean off-road glance time), and increasing performance (shortest interaction times, highest number of correct responses and least 'overshoots') associated with continuous tasks. In contrast, for discrete, target-selections, the touchscreen enabled the highest accuracy and quickest responses, particularly when combined with haptic feedback to guide interactions, although this also increased visual demand. Subjectively, the gesture interfaces invited higher ratings of arousal compared to the more familiar touch-surface technology, and participants indicated the lowest levels of workload (highest performance, lowest frustration) associated with the gesture-haptics interface. In addition, gestures were preferred by participants for continuous tasks. The study shows practical utility and clear potential for the use of haptified gestures in the automotive domain.